STUDI AWAL GAMBARAN PENGETAHUAN DASAR DAN SIKAP WISATAWAN BACKPACKER MANCANEGARA DI BALI MENGENAI RESIKO INFEKSI RABIES - Agustina, I Gede Eddy Pramana (E-Jurnal Medika Udayana; Vol 5 No 5 (2016): E-jurnal medika udayana, 2016)
Since Bali establish as rabies endemic area in 2008, all people in Bali have high risk for getting rabies infection, those are including foreign tourists who come to Bali. Backpacker is one who has high risk of infection because of their habitation of getting their destination on foot and travelling with limiting budget. This study describes the basic knowledge and attitude of foreign backpacker regarding rabies infection prevention with deep interview based on preprinted questioners. This study uses cross sectional design held on December 2013to February 2014 with 56 samples. We get 92,8% foreign backpacker who travelling in Bali do not know that Bali is a rabies endemic area, 82,1% foreign backpacker who travelling in Bali  do not know how to avoid rabies infection, 7,1% foreign backpacker who travelling in Bali do not know dog as main carrier rabies in Bali, 64,3% foreign backpacker who travelling in Bali  did not get information regarding rabies risk, initial management of biting before trip and 92,9% foreign backpacker who travelling in Bali  did not receive complete rabies vaccine shot before travelling in their country.
Keywords: Backpacker, Rabies